Distinct Wrist Patterns Founded on Measurements in Plain Radiographs - Kramer, Aviv; Allon, Raviv; Werner, Frederick; Lavi, Idit; Wolf, Alon; Wollstein, Ronit (Journal of Wrist Surgery, 2018)
Background In joints, structure dictates function and consequently pathology. Interpreting wrist structure is complicated by the existence of multiple joints and variability in bone shapes and anatomical patterns in the wrist. Previous studies evaluated lunate and capitate shape in the midcarpal joint, and two distinct patterns have been identified.Purpose Our purpose was to further characterize the two wrist patterns in normal wrist radiographs using measurements of joint contact and position. Our hypothesis was that we will find significant differences between the two distinct anatomical patterns.Patients and Methods A database of 172 normal adult wrist posteroanterior (PA) radiographs was evaluated for radial inclination, height, length, ulnar variance, volar tilt, radial-styloid-scaphoid distance, and lunate and capitate types. We measured and calculated percent of capitate facet that articulates with the lunate, scapholunate ligament, scaphoid, and trapezoid. These values were compared between the wrist types and whole population.Results Type-1 wrists (lunate type-1 and spherical proximal capitate) were positively associated with a longer facet between capitate and distal lunate (p = 0.01), capitate and base of middle metacarpal (p = 0.004), and shorter facet between the capitate and hamate (p = 0.004). The odds ratio of having a type-1 wrist when the interface between the capitate and lunate measures >8.5 mm is 2.71 (confidence interval [CI] 1.07, 6.87) and when the line between the capitate and the base of middle metacarpal >9.5 mm is 3.5 (CI 1.38, 9.03).Conclusion We characterized the two-wrist patterns using intracarpal measurements. Translating these differences into three-dimensional contact areas may help in the understanding of biomechanical transfer of forces through the wrist.Level of Evidence This is a Level II, diagnostic study.
Keywords: bony anatomy; biomechanics; patterns; shape; wrist